Towards Sustainable Dispute Resolution: A Framework to Enhance the Application of Fast Track Arbitration in the Malaysian Construction Industry - Muhd Fadhlullah Ng, Nur Khodijah; Ismail, Zulhabri; Hashim, Fashiha (International Journal of Sustainable Construction Engineering and Technology, 2020)
There is a significant increase in the role of construction industry for the last few decades accompanied by a considerable upsurge in the construction disputes as well. Arbitration has constantly become popular, and strengthened its position as it can be settled within the stipulated time compared to litigation. However, the arbitral process takes longer which leads to fast track arbitration. Fast track arbitration is designed to enable arbitration to proceed quickly, which can minimize the time and optimize the cost. The proliferation number of construction disputes from construction industry has emerged the importance in using fast track arbitration as one of the preferable Alternative Dispute Resolution (ADR). Regardless of frequent developments made to overcome the issues, however, there is an insignificant figure on the usage of fast track arbitration in the construction industry. This paper therefore aims to elicit a better understanding of the application of fast track arbitration in the Malaysian construction industry. Twenty (20) total number of participants – construction arbitrators – were interviewed to record their experience. A proposed framework for the application of fast track arbitration has been constructed from the responses to expand the current definition. With the changing practice environment, construction arbitrators need to be aware of the existing fast track arbitration which is crucial in ensuring its efficiencies to be applied in Malaysia, and this paper is intended to aid this process.